ATHEMATICAL MODEL FOR THE OPTIMISATION OF HIERARCHICAL MULTI-LEVEL PRODUCTION SYSTEMS - Yu. V. Minaeva (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives The aim of the study is to develop a mathematical model for the complex solution of various problems in designing and reconstructing the technological system of a production workshop of a machine-building enterprise.Methods Complex system theory and an aggregative decomposition approach are used as the methodological basis for modelling complex hierarchical productions, making it possible to represent a complex system in the form of a set of interconnected subsystems.Results A mathematical model designed for a complex solution of problems associated with the formation of an optimal production programme and selection ofequipment was developed. Operative parameters for processing machines according to a single optimisation criterion for the workshop were established. Distinctive features of the optimisation model proposed in the article are the possibility of its application both for design and for the reconstruction of a technological system, as well as the possibility of simple scaling to the required level (i.e. the workshop as a whole or a separate section).Conclusion The article presents a complex mathematical model for optimising the technological system based on a single optimisation criterion for the workshop, combining the solution of the main tasks of design and reconstruction of the workshop. The use of a single integral optimisation criterion for several problems allows the strong interrelationships between individual tasks to be taken into account. The model is based on the principle of arranging a model from a set of typical elements, easing the construction of models for any sub-task combinations, as well as their respective options. It is possible to use the model’s multi-level unification and scalability to increase modelling efficiency and thus optimise complex multinomenclature productions.